Resonance methods for the characterization of dust particles in plasmas. (4th May 2016) - Jung, Hendrik; Greiner, Franko; Asnaz, Oguz Han; Carstensen, Jan; Piel, Alexander
Abstract : The fundamentals of the 'resonance method' are presented. The method relies on evaluating the dynamic response of one or more dust particles in the sheath of a laboratory plasma to small external perturbations. It allows one to make in situ high-precision measurements of particle properties. It is shown that the particle mass and charge and the strength of the interaction between two particles can be measured. Technical requirements, limitations and application examples are presented and discussed.